Penerapan SAK EMKM Pada Penyusunan Laporan Keuangan UMKM Studi Kasus Pada UD Fais Jaya - Adelia Febriana; Cholis Hidayati (Akuntansi, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the economic activities carried out by some Indonesian people and play an important role in the Indonesian economy. The purpose of this research is to apply SAK EMKM as the basis for preparing financial statements at UD Fais Jaya MSMEs. This study uses a qualitative descriptive design research method by collecting data by conducting interviews, observations, and direct documentation with business owners. The results of this study indicate that the financial recording system that occurs is very simple, has not implemented financial reports and the importance of preparing financial reports in accordance with SAK EMKM due to a lack of understanding of the formal financial recording process, because it is considered quite difficult and complicated to apply to its business and limited knowledge about financial reports and training on these reports.